A NEW RECORD OF Cephalopholis igarashiensis KATAYAMA, 1957 (PERCIFORMES, SERRANIDAE) FROM INDONESIA - T. Peristiwady; M. F. Rahardjo; C. P.H. Simanjuntak (Jurnal Iktiologi Indonesia, 2009)
Four specimens were collected at Winenet Fish Market, Bitung, North Sulawesi, Indonesia on March 5th, 2008 and October 11th, 2009. Other one specimen was collected at Batuputih Fish Market on October 17th, 2009. The fish was caught by hook and line at a depth about 50 m in Dua Island, North Sulawesi. Distribution of Cephalopholis igarashiensis at Pacific Ocean is found in southern Japan, Taiwan, Guam, Philippines, South China Sea, Samoa, and Tahiti in French Polynesia. Its morphological features and diagnostic characters are discussed and illustrated.